LEVERAGING TECHNOLOGY AND POLICY IN WEST JAVA POULTRY PRODUCTION - Ridlo Aminuddin, Rahmat
This research analyses the constraints on supply chain processes within the poultry industry in West Java, Indonesia. During the upstream process, the mortality rate of chickens often surpasses 5% due to several factors including stocking density. Another identified problem adversely affecting the upstream process is the inability of small-scale farmers to procure their own Grand Parent Stock (GPS) since they remain dependent upon corporations to supply it, leading to inefficiency and increased production costs. Meanwhile, in downstream processes, the lack of a cold supply chain system and adequate storage capacity presents other challenges with regard to product durability. Technology and policy implementation constitutes one of the solutions implemented to address these problems. This research adopts a soft system methodology (SSM) in order to identify the problems confronting poultry supply chain actors in West Java. The data was collected through interviews and FGD with the government and poultry supply chain actors such as slaughterhouse and poultry farm owners. On the basis of the identified problems, we propose a conceptual model highlighting those factors which optimise the poultry supply chain. We also simulate the proposed model to find out how technology and policy affect the production process using system dynamics (SD). The simulation shows that there is a significant supply increase if both technology and policy are implemented in the system. This research contributes to theoretical knowledge by observing the outcome of technology and policy implementation in the poultry food supply chain. Managers could also benefit from this research by investing in technology to boost productivity.